Tau and delirium superimposed on dementia: A case report - Po-Chung Yu; Ching-Min Kuo; I-Chun Chen (SAGE Open Medical Case Reports, 2024)
We present a case involving a 60-year-old man with subacute delirium characterized by challenging attention shifts and obstinate behavior, contrasting with his usual mild-mannered personality. The patient developed pneumonia and a urinary tract infection following the onset of subacute delirium. Despite exhaustive investigations, the cause remained elusive until cerebrospinal fluid analysis revealed Tau positivity. Our overview suggests neurodegenerative diseases as the primary cause, rather than infectious or autoimmune factors. The case underscores a significant association between Tau and delirium superimposed on dementia, offering guidance to clinicians managing such patients.